(untitled) (Cambridge, UK, 2016)
The book is a comprehensive source of physics-based models for the analysis of progressive and critical failure phenomena in composite materials, and focuses on materials modeling, while also reviewing treatments to give the reader thorough direction for analyzing failure in composite structures. Part one of the book reviews the damage development in composite materials such as generic damage and damage accumulation in textile composites and under multiaxial loading, while part two focuses on the modeling of failure mechanisms in composite materials with attention given to fibre/​matrix cracking and debonding, compression failure, and delamination fracture
Keywords: Vật liệu tổng hợp,Composite materials; Mô hình toán học,Mathematical models